Social health and dementia: a European consensus on the operationalization of the concept and directions for research and practice. (2nd January 2017) - Dröes, R.M.; Chattat, R.; Diaz, A.; Gove, D.; Graff, M.; Murphy, K.; Verbeek, H.; Vernooij-Dassen, M.; Clare, L.; Johannessen, A.; Roes, M.; Verhey, F.; et al.
ABSTRACT: Background: Because the pattern of illnesses changes in an aging population and many people manage to live well with chronic diseases, a group of health care professionals recently proposed reformulating the static WHO definition of health towards a dynamic one based on the ability to physically, mentally and socially adapt and self-manage. This paper is the result of a collaborative action of the INTERDEM Social Health Taskforce to operationalize this new health concept for people with dementia, more specifically the social domain, and to formulate directions for research and practice to promote social health in dementia. Method: Based on the expertise of the Social Health Taskforce members ( N = 54) three groups were formed that worked on operationalizing the three social health dimensions described by Huber et al.: (1) capacity to fulfil potential and obligations; (2) ability to manage life with some degree of independence; (3) participation in social activities. For each dimension also influencing factors, effective interventions and knowledge gaps were inventoried. After a consensus meeting, the operationalizations of the dimensions were reviewed by the European Working Group of People with Dementia (EWGPWD). Results: The social health dimensions could be well operationalized for people with dementia and are assessed as very relevant according to the Social Health Taskforce and EWGPWD. Personal (e.g. sense of coherence, competencies), disease-related (e.g. severity of cognitive impairments, comorbidity), social (support from network, stigma) and environmental factors (e.g. enabling design, accessibility) that can influence the person with dementia's social health and many interventions promoting social health were identified. Conclusion: A consensus-based operationalization of social health in dementia is proposed, and factors that can influence, and interventions that improve, social health in dementia identified. Recommendations are made for research and practice.